Recycled glass and Ce‐Doped‐Y3Al5O12 nanoparticles phosphor‐in‐glass for white light‐emitting diodes applications - Chapa, Christian (2020)
A series of nanocomposites of recycled soda‐lime glass from a glass container and Y3Al5O12:Ce3+ (YAG:Ce) phosphor nanoparticles are fabricated by the two‐step low‐temperature co‐sintering technology. A transparent glass bottle from a commercial beverage is used as glass frit source and mixed with YAG:Ce nanoparticles. Afterward, the powders are pressed to obtain pellets with phosphor concentrations in the range of 2.5–15 wt%. The pellets are sintered at 800 and 900 °C. X‐ray diffraction (XRD) analysis shows that YAG:Ce nanoparticles are conserved even after sintering at 900 °C. The XRD analysis shows that YAG:Ce nanoparticles are conserved even after sintering at 900 °C. The emission spectra of the Ce3+ ions of yttrium aluminum garnet (YAG) nanoparticles combined with the transmitted blue light exhibit color tuning related to the phosphor concentration and the sintering temperature. A tonality shift from cold‐white light toward yellowish‐green region is observed according to the estimated CIE 1931 chromaticity. Thus, recycled glass from a commercial glass container and YAG:Ce nanoparticles phosphor‐in‐glass (PiG) can be an eco‐friendly and low‐cost alternative as color converters.